Porównaj: 75% liczby a i 45% liczby b, gdy
a = (3 1/3 + 3) : 2 - 1/6

b = 3 1/3 + (3:2 - 1/6)​



Odpowiedź :

Najpierw obliczmy wartości a i b:

a = (3 1/3 + 3) : 2 - 1/6 = 6 1/3 : 2 - 1/6 = 6 2/6 : 2 - 1/6 = 3 1/6 - 1/6 = 3

b = 3 1/3 + ( 3 : 2 - 1/6 ) = 3 1/3 + (3/2 - 1/6) = 3 1/3 + (9/6 - 1/6) = 3 1/3 + 8/6 = 3 2/6 + 8/6 = 20/6 + 8/6 = 28/6 = 4 4/6 = 4 2/3

75% z 3:

3 * 0,75 = 3/1 * 75/100 = 225/100 = 2,25

45% z 4 2/3:

14/3 * 0,45 = 14/3 * 45/100 = 14/1 * 15/100 = 210/100 = 2,1

2,25 > 2,1

75% z 3 jest większe od 45% z 4 2/3